RUSSIAN ACCENT IN BRAZILIAN PORTUGUESE AFFECTS THE PERCEPTION OF VOICE PLEASANTNESS BY BRAZILIANS - Smirnova Henriques, Anna; Madureira, Sandra (Revista X, 2020)
The field of foreign accents in Brazilian Portuguese is very poorly explored mainly in relation to perceptual impressions caused on listeners by foreign accents. The objective of this paper is to conduct a perceptual experiment to analyze the perception of voice pleasantness in relation to degrees of foreign accent. Our focus is on Russian accented Brazilian Portuguese. Despite the representativeness of the Russian community in Brazil, there are hardly any studies on Russian accented speech. To evaluate the perception of voice pleasantness in relation to the Russian accented speech, we have selected, from our database, speech samples in Brazilian Portuguese from 12 native Russian speakers and six Brazilians, all of them residing in São Paulo. The speech samples were incorporated into an online questionnaire. The analysis of the 129 answers given by the native Brazilian Portuguese speakers showed a strong negative correlation between the degree of Russian accent in Brazilian Portuguese and the degree of voice pleasantness. Experience of interaction with foreigners or knowledge of foreign languages, including Russian, did not influence the result. We conclude that higher degrees of Russian accented speech in Brazilian Portuguese affect the perception of speakers´ characteristics by Brazilians in a negative way.